2010
DOI: 10.3846/bjrbe.2010.22
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Cellulose Fibres and Waste Plastic Modified Porous Friction Course Mixes

Abstract: Th is paper summarises the laboratory investigation on porous friction course mixes that were modifi ed with cellulose fi bres and waste plastics. Porous friction course mixes of three diff erent aggregate gradations were tested for predetermined binder content. Th e infl uence of each modifi er on the volumetric properties, permeability, aged abrasion loss, and moisture susceptibility of porous friction course mixes were evaluated. In order to determine the signifi cance level of eff ect of modifi ers on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…), material heterogeneity (RAP Asphalt Content & Gradation) and other sources of variations caused RAP variability [23][24][25][26][27][28]. Despite this, it is noted that due to the use of a very high percentage of RAP, experiments demonstrate that the solutions proposed meet a number of sustainability requirements [29][30][31]. Furthermore, these facts illustrate the potential and suitability of the designed mixes for improved pavement life cycles [32][33][34][35].…”
mentioning
confidence: 99%
“…), material heterogeneity (RAP Asphalt Content & Gradation) and other sources of variations caused RAP variability [23][24][25][26][27][28]. Despite this, it is noted that due to the use of a very high percentage of RAP, experiments demonstrate that the solutions proposed meet a number of sustainability requirements [29][30][31]. Furthermore, these facts illustrate the potential and suitability of the designed mixes for improved pavement life cycles [32][33][34][35].…”
mentioning
confidence: 99%
“…Another crucial property is the particle size and shape of WPs. Plastic can be added to HMA in many shapes with varied sizes, such as powder (0.035-0.25 mm) [21,22], pellets (5-10 mm) [23], fibers (6.5-30 mm) [24][25][26], flakes (0.63-10 mm) [27][28][29][30], or granules (0.3-0.6 mm) [31,32]. WPs can also go through some processes for size reduction, such as shredding, grinding, crushing, and cutting [10,[33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Also evolved in resistance to moisture damage occurred. Suresha et al [28] reported that the use of cellulose fiber gives positive outcomes appreciably, so it contributed to decreasing the drain down and Cantabro abrasion results. Also, the moisture susceptibility was improved, but it led to a decrease the permeability.…”
Section: Introductionmentioning
confidence: 99%